Emery and Rimoin's Essential Medical Genetics - Rimoin, David L (Elsevier, Academic Press, 2013)
For decades, Emery and Rimoin's Principles and Practice of Medical Genetics has provided the ultimate source for practicing clinicians to learn how the study of genetics can be integrated into practice. Developed in parallel to the sixth edition, and featuring 174 original contributions from the many authors of the full set, this one volume work expertly condenses and synthesizes the most clinically relevant content, for convenient desk reference. Helping to bridge the gap between high-level molecular genetics and individual application, it follows the multi-volume set in encompassing scientific fundamentals, full spectrum discussion of major inherited disorderd, and actionable therapies.